Prologue - Corré, Alan; Castellanos, Carles (My University, 2010)
This is a translation into English from Catalan of the Prologue to "La Lingua Franca. Consideracions crtiques" by Carles Castellanos. It describes the development of Lingua Franca, with special reference to sources in Occitan-Catalan.
From: La Lingua Franca. Consideracions crtiques. Traducci del document Proves documentals de la Lingua Franca de Christian Foltys amb prleg i notes de Carles Castellanos. Girona: 2006
Keywords: Pidgins and Creoles; Lingua Franca